2018
DOI: 10.1111/aji.12812
|View full text |Cite
|
Sign up to set email alerts
|

Soluble CD14 levels in plasma and breastmilk of Malawian HIV+ women: Lack of association with morbidity and mortality in their exposed infants

Abstract: Higher sCD14 levels in HIV-positive women were associated with a more compromised maternal immunological status and to a lower neonatal birthweight, but not to poorer clinical outcomes in the HIV-exposed children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…Although many studies conducted in Africa reported higher levels of inflammatory markers in HIV infected individuals with respect to their seronegative counterparts [8,30,31], others found contrasting results; no correlation between HIV progression and sCD14 and LPS levels was found in Ugandan patients, that also had concentrations of sCD14 and LPS similar to those of matched seronegative Afro-American individuals [32]; similarly, a trend toward lower levels of I-FABP in HIV-positive participants compared to HIVuninfected individuals has been observed in a sub Saharan cohort, suggesting differential relationships among biomarkers of intestinal barrier integrity and innate immune activation [33]. In a recent study, our group found levels of sCD14 lower than expected in Malawian HIV pregnant women prior to ART treatment, but still associated to the immune virological parameters and to low birth weight [17]. The interpretation of these results is difficult since the difference in inflammatory markers could be related to other factors such as hygiene and sanitation levels and/or common exposure to other gastrointestinal infections or parasites.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Although many studies conducted in Africa reported higher levels of inflammatory markers in HIV infected individuals with respect to their seronegative counterparts [8,30,31], others found contrasting results; no correlation between HIV progression and sCD14 and LPS levels was found in Ugandan patients, that also had concentrations of sCD14 and LPS similar to those of matched seronegative Afro-American individuals [32]; similarly, a trend toward lower levels of I-FABP in HIV-positive participants compared to HIVuninfected individuals has been observed in a sub Saharan cohort, suggesting differential relationships among biomarkers of intestinal barrier integrity and innate immune activation [33]. In a recent study, our group found levels of sCD14 lower than expected in Malawian HIV pregnant women prior to ART treatment, but still associated to the immune virological parameters and to low birth weight [17]. The interpretation of these results is difficult since the difference in inflammatory markers could be related to other factors such as hygiene and sanitation levels and/or common exposure to other gastrointestinal infections or parasites.…”
Section: Discussionsupporting
confidence: 73%
“…Inflammation during pregnancy can increase the risk of preterm delivery and intrauterine growth retardation [9,13,14] in HIV pregnant women elevated levels of sCD14 have been associated to risk of maternal to child transmission (MTCT) [15], preterm delivery and low birth weight [16,17]. Since most of HIV women of childbearing age live in low-income countries [18], investigating the biomarkers profile of immune activation of these populations should be a priority, also considering the profound impact that maternal inflammation could have on neonatal outcomes [19].…”
Section: Introductionmentioning
confidence: 99%
“… 15 Increased levels of sCD14 were also found to be associated with reduced birth weight among 149 women living with HIV in Malawi. 17 A case-control study conducted in Ethiopia, India, and Uganda found that increased intestinal barrier dysfunction (I-FABP) and microbial translocation/monocyte activation (sCD14 and sCD163) increased odds of preterm birth, but CRP was not associated. 16 Overall, evidence on the relationship of maternal EED with birth outcomes is mixed, and the strength of the relationships may differ by maternal HIV status.…”
Section: Discussionmentioning
confidence: 99%
“…Small case-control studies among PWLHIV in Spain and India have reported that increased lipopolysaccharide-binding protein (LBP), soluble CD14 (sCD14), soluble CD163 (sCD163), and intestinal-fatty acid binding protein (I-FABP) were associated with increased risk of preterm birth, 15 , 16 and a small cohort study in Malawi found increased sCD14 was associated with lower birthweight. 17 However, a recent cohort study in India among pregnant women with and without HIV that examined these same biomarkers (sCD14, CD163, and I-FABP) did not find associations with low birthweight or preterm birth, either among all women regardless of HIV status or among women living with HIV. 18 To our knowledge, no studies have examined the relationship of biomarkers of EED among PWLHIV and stillbirth, an important yet understudied adverse birth outcome.…”
Section: Introductionmentioning
confidence: 93%
“…Several soluble receptors involved in the modulation of gut inflammation are also present in HM. Cluster of differentiation 14 is a membrane receptor that is secreted (sCD14) upon cell activation and regulates the function of epithelial cells by interfering with endogenous or microbial pro-inflammatory signaling (Baroncelli et al, 2018). Transforming growth factor β (TGF-β) is a cytokine capable of increasing the production of IgA, contributing to oral tolerance mechanisms (Oddy and Rosales, 2010) and reinforcing the epithelial barrier by acting as a growth factor.…”
Section: Introductionmentioning
confidence: 99%